Meropenem: a potent drug against superbug as unveiled through bioinformatics approaches. (1st January 2013) - Mallick, Medhavi; Odedra, Devang; Vidyarthi, Ambarish Sharan; ,
Global spread of multi-drug resistant bacteria like Klebsiella pneumoniae and Escherichia coli have raised the alarm for researchers and doctors throughout the world. This new mechanism of resistance and the ability of ndm-1 gene to be transferred between the species may end the era of antibiotics treatment. Carbapenems are reliable drugs against many multi-resistant gram-negative pathogens. A 3-D homology model of NDM-1 was built and analysed for elucidation of functional site and binding interactions. This study revealed that meropenem has good interaction with the active sites of the receptor that could retard the spread of antibiotic resistant bacteria.